MAIN MOLECULAR TARGETS FOR PROSTATE CANCER THERAPY - G. S. Krasnov; A. A. Dmitriev; N. N. Volchenko; T. V. Danilova; A. F. Sadritdinova; A. V. Snezhkina; N. V. Melnikova; M. S. Fedorova; V. A. Lakunina; A. A. Belova; B. Y. Alekseev; A. D. Kaprin; et al. (Сибирский онкологический журнал, 2016)
Androgenic pathway plays a pivotal role in the development of benign and malignant prostate tumors. Most of the prostate neoplasms are hormone-dependent at the time of diagnosis. Therapeutic interventions aimed at reducing the level of testosterone in the blood allow to stop progression of the disease. But over time, the tumor almost inevitably starts to progress, moving in the castration-resistant state (CRPC), representing a serious problem of oncourology. In recent years, the possibility of CRRPC therapy increased significantly – there was developed a number of new drugs that effectively inhibit the development of castration-resistant tumors and significantly push back the start of chemotherapy. This review describes the major drug targets and mechanisms of action of abiraterone, enzalutamide, galeterone, VT-464 and other approved and promising CRPC therapies.